The effects of interfacial exchange coupling in Fe/ErFeO3 heterostructures. (21st April 2017) - Tang, J; Ke, Y J; He, W; Zhang, X Q; Zhang, Y S; Zhang, W; Li, Y; Ahmad, S S; Cheng, Z H
Abstract: Exploring exchange bias in ferromagnetic (FM)/antiferromagnetic (AFM) heterostructures is vital for both fundamental magnetism and practical application. However, in the case of conventional FM/AFM systems, the essential field cooling process above the Néel temperature of AFM materials hinders their application if the Néel temperature is far higher than room-temperature. Here, we report the effects of interfacial exchange coupling in Fe/ErFeO3 heterostructures. The magnetic-field-induced switchable exchange bias, originating from the AFM exchange coupling between Fe film and Dzyaloshinskii–Moriya-interaction-induced net moment of ErFeO3 along c axis, is successfully achieved without field cooling or in-field growth process of AFM. Different from the most previous pinning layer using a hard FM or traditional AFM, ErFeO3 pinning layer has the advantages of both the magnetic field sensitivity ( 780 Oe) and ultrahigh dynamic frequency. In addition, although Fe film is polycrystalline, it exhibits a strong uniaxial magnetic anisotropy resulted from the so-called 'spin-flop-coupling effect', i.e. the magnetic coupling between Fe film and the compensated G -type AFM spins of EFO along a axis. Interestingly, the exchange bias field and asymmetric switching field offer entirely different information about the asymmetry of magnetization reversal near hard axis. The asymmetric switching field is further proved to be an effective measure to determine the weak unidirectional magnetic anisotropy for film with nearly 180° domain wall displacement. Our experimental results provide a practical method to establish room-temperature exchange bias in FM/ G -type AFM without field cooling. Furthermore, the magnetic-field-induced switchable exchange-bias, the spin-flop coupling effect and the angular dependent asymmetry of magnetization reversal in the vicinity of hard axis in Fe/ErFeO3 heterostructures may provide new insights on the interfacial exchange coupling in FM/AFM systems.